Why Environmental Conflicts Can Be Productive: The Conflict Over the Environmental Restoration of the Matanza-Riachuelo River Basin in Buenos Aires - Merlinsky, Maria Gabriela (2020)
The purpose of this paper is exposing our approach for the study of environmental conflict and show illustrations from our research work on the conflict over the environmental restoration of the Matanza-Riachuelo River Basin. We will be referring to the conflicts´ territorial effects of the conflict and we will seek to raise some questions to nourish the debate on the metropolitan environmental issue.